Oropharyngeal Squamous Cell Carcinoma: Human Papilloma Virus Coinfection with Streptococcus anginosus - Robayo,Dabeiba Adriana Garcia (2019)
Abstract Introduction: Human papilloma virus (HPV) and oral bacteria capable of acetaldehyde production from ethanol, such as Streptococcus anginosus, Prevotella melaninogenica, and Fusobacterium naviforme are among oropharyngeal squamous cell carcinoma (OSCC) infectious risk factors. Objective: Determine associations with HPV and S. anginosus, P. melaninogenica, and F. naviforme in patients with and without OSCC. Methods: Presence of HPV and HPV-16 was determined in 26 patients with OSCC and 26 without OSCC by conventional PCR and simultaneous presence of S. anginosus, P. melaninogenica, and F. naviforme quantification through q-PCR. Statistical analysis was carried out using Pearson’s X² and Student’s-t test. Results: Patients with OSCC had HPV and HPV-16 frequencies of 84% and 61.5%, respectively, in contrast for patients without OSCC frequencies were 34.6 and 30.7%. P. melaninogenica, and F. naviforme microorganisms were not present in any participant in this study. S. anginosus frequency in patients with OSC was 38.4% and in patients without OSCC was 30.7%. Patients with OSCC had S. anginosus + HPV co-infection at a 38.4% frequency and S. anginosus + HPV-16 at a 23.1% frequency. For individuals without OSCC S. anginosus + HPV co-infection was 3.8% and S. anginosus + HPV-16 3.8%. A greater frequency of S. anginosus + HPV co-infection and S. anginosus + HPV-16 was observed in patients with OSCC in comparison with individuals without OSCC, suggesting the importance of detecting HPV/HPV-16 and S. anginosus simultaneously in individuals at risk of developing OSCC